Teachers’ emotional experiences and exhaustion as predictors of emotional labor in the classroom: an experience sampling study - Keller, Melanie M.; Chang, Mei-Lin; Becker, Eva S.; Goetz, Thomas; Frenzel, Anne C. (Frontiers in Psychology, 2014)
Emotional exhaustion is the core component in the study of teacher burnout, with significant impact on teachers’ professional lives. Yet, its relation to teachers’ emotional experiences and emotional labor during instruction remains unclear. Thirty-nine German secondary teachers were surveyed about their emotional exhaustion (trait), and via the Experience Sampling Method on their momentary (state; N = 794) emotional experiences (enjoyment, anxiety, anger) and momentary emotional labor (suppression, faking). Teachers reported that in 99% and 39% of all lessons, they experienced enjoyment and anger, respectively, whereas they experienced anxiety less frequently. Teachers reported suppressing or faking their emotions during roughly a third of all lessons. Furthermore, emotional exhaustion was reflected in teachers’ decreased experiences of enjoyment and increased experiences of anger. On an intra-individual level, all three emotions predict emotional labor, whereas on an inter-individual level, only anger evokes emotional labor. Explained variances in emotional labor (within: 39%, between: 67%) stress the relevance of emotions in teaching and within the context of teacher burnout. Beyond implying the importance of reducing anger, our findings suggest the potential of enjoyment lessening emotional labor and thereby reducing teacher burnout.